A high-power, high-temperature resistant piezoelectric ceramic and its preparation method
Through the liquid -phase wrapped solid phase and osmotic technology, high -power high -temperature voltage -resistant ceramics are prepared, which solves the problem of insufficient performance in the existing technology in high -temperature and high -power environments, and realizes the efficient preparation and excellent performance of ceramics.
Patent Information
- Application Number
- CN202411237685.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The prior art is difficult to meet the performance requirements of piezoelectric ceramics in high power and high temperature environments, and the preparation process is complex and the efficiency is low.
The method of liquid -phase wrapping solid phase is used to prepare ceramic powder, and the powder and sintering are sintering through the dry pressure of the powder, and the hard osmotic factor and high temperature osmotic factor are added to achieve uniform penetration and molecular -level composite.
The preparation of high -power high -temperature -resistant voltage -resistant ceramics in high temperature and high -power environments is better than existing technology products in high -temperature and high -power environments, and it is simple and efficient, suitable for large -scale industrialized production.
Smart Images

Figure CN118754656B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric ceramics, and in particular to a high-power high-temperature resistant piezoelectric ceramic and a preparation method thereof. Background Art
[0002] Piezoelectric ceramics can realize the mutual conversion of electrical energy and mechanical energy. Due to its excellent performance in fast response to voltage input, high stiffness and large output force, it is a high-quality material for the preparation of ultrasonic surgical knife transducers. The high-voltage electricity conversion efficiency, stability and durability make piezoelectric ceramics an important choice for medical device manufacturers. With the continuous development and innovation of science and technology, its application areas will continue to expand. Low-power piezoelectric devices can no longer meet the needs of modern development, and high-power has become an important development direction for piezoelectric devices.
[0003] With the increasingly widespread application of piezoelectric ceramics, piezoelectric ceramics have been continuously developed, mainly in terms of doping, technology and the search for higher-element composites. Therefore, the piezoelectric dielectric properties of binary and ternary piezoelectric ceramics can no longer meet the requirements of various fields. The development of high-performance multi-element piezoelectric ceramics has received widespread attention. After ion doping, the ions dissolved in the grains will increase the free energy of the system, thereby increasing the sintering driving force. The ions segregated on the grain boundaries will form low-melting point compounds, thus becoming the "adhesive" between the grains and reducing the solid-phase reaction temperature. Therefore, finding a suitable doping factor is one of the effective ways to improve the performance of piezoelectric ceramics.
[0004] At the same time, in the actual production process, the performance of piezoelectric ceramics depends largely on the preparation process used and the process parameters selected. Only under the optimal process parameters can the performance of piezoelectric ceramics be fully exerted. The process flow of preparing piezoelectric ceramics mainly includes powder preparation process, molding process and sintering process. The preparation of powder is very important to the quality of piezoelectric ceramics. In order to ensure the excellent performance and stability of piezoelectric ceramic products, ceramic powders must have the following characteristics: 1) Accurate chemical composition, which directly determines the crystal phase and performance of the product; 2) Good uniformity of chemical composition to avoid local crystal phase segregation and microstructural differences, affecting product quality; 3) High purity to ensure the piezoelectric performance of the product; 4) Appropriately small particle size can improve the sintering performance of ceramics. However, the performance of piezoelectric ceramic products prepared by existing technical methods still needs to be further improved. Summary of the invention
[0005] In view of the above-mentioned defects in the prior art, the present application first provides a method for preparing high-power high-temperature resistant piezoelectric ceramics, which mainly adopts a method for preparing ceramic powder by liquid-encapsulating solid phase, and then obtains high-power high-temperature resistant piezoelectric ceramics by dry pressing the powder and sintering at normal pressure. The present application also provides a piezoelectric ceramic product prepared by the above method.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] In the first aspect, the present application provides a method for preparing a high-power high-temperature resistant piezoelectric ceramic: the high-power high-temperature resistant piezoelectric ceramic is a lead zirconate titanate piezoelectric ceramic with an impurity factor added, and the general formula of the matrix is: Pb(Zr x Ti (1-x) )O3, wherein 0.4≤x≤0.6, the impurity factor is specifically a hard impurity factor and a high temperature impurity factor, and the preparation method comprises the following steps:
[0008] According to the matrix general formula, two of the water-soluble zirconium source, titanium source and lead source are weighed and dissolved in deionized water and stirred to form a solution, and one of the water-insoluble zirconium source, titanium source and lead source and a doping factor are added and mixed and stirred to obtain a suspension;
[0009] ball milling the suspension to obtain a ceramic slurry;
[0010] The ceramic slurry is spray-dried to obtain primary powder;
[0011] The primary powder is placed in a sealed high-temperature sintering furnace for heating reaction to obtain a ceramic powder;
[0012] The ceramic powder is subjected to pressing, sintering, electrode application and polarization treatment to obtain high-power high-temperature resistant piezoelectric ceramics.
[0013] In one embodiment of the present application, the zirconium source is one or more of zirconium dioxide, zirconium nitrate, and zirconium acetate; the titanium source is one or more of titanium dioxide, titanium oxalate, and titanium citrate; and the lead source is one or more of lead tetroxide, lead nitrate, and lead peroxide.
[0014] In one embodiment of the present application, the content of the doping factor is 0.1-10wt% of the matrix.
[0015] In one embodiment of the present application, the mass ratio of the hard impurity factor to the high temperature impurity factor is 0.5~2:1.
[0016] In one embodiment of the present application, the hard impurity factor is one or more of manganese antimonate, magnesium niobate, manganese niobate, and zinc niobate; the high-temperature impurity factor is one or more of bismuth manganate, bismuth ferrite, bismuth scandate, and calcium ferrite.
[0017] In one embodiment of the present application, the particle size of the solid powders such as the zirconium source, titanium source, lead source, and impurity factors is in the range of 10-40 μm, and the D50 of the solid material particles in the ceramic slurry after ball milling is 0.5-2 μm.
[0018] In one embodiment of the present application, when there are two or more hard impurity factors, the masses of all hard impurity factors are equal.
[0019] In one embodiment of the present application, when there are two or more high-temperature doping factors, the masses of all high-temperature doping factors are equal.
[0020] In one embodiment of the present application, the preparation method further comprises adjusting the solid content of the suspension to 40-80% using deionized water.
[0021] In one embodiment of the present application, the ball milling time is 60-200 min.
[0022] In one embodiment of the present application, the specific conditions of the heating reaction are: reaction at 600-1000° C. for 1-4 hours, and a heating rate of 3-5° C. / min.
[0023] In a second aspect, the present application provides a product obtained by any of the above-mentioned methods for preparing high-power high-temperature resistant piezoelectric ceramics.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The preparation method of high-power high-temperature resistant piezoelectric ceramics provided by the present invention is to fully and evenly diffuse and transfer each other between components through solid-liquid mixing combined with ball milling, thereby achieving sufficient mass transfer between components, achieving composite and homogenized balance at the molecular level, adjusting the activity of each reactant, overcoming the problems caused by component diversity, and preparing pure phase ceramic powder. In addition, the applicant uniformly mixes the hard impurity factor and high-temperature impurity factor obtained by experimental screening into the ceramic matrix on the basis of solid-liquid mixing combined with ball milling, so that the free energy of the system changes, thereby changing the configuration and structure of the domain, reducing the unevenness of the ceramic microstructure, and improving the sintering density. The stability and high temperature resistance of the obtained high-power piezoelectric ceramics in a high-power environment are better than those of the products of the prior art. In addition, the process of the present invention is simple and flexible, the solid-phase reaction temperature is low, the efficiency is high, the repeatability is good, and it is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD test image of the piezoelectric ceramic prepared in Example 1 of the present invention (pure phase);
[0027] Figure 2 This is a scanning electron microscope image of a cross section of a piezoelectric ceramic prepared in Example 1 of the present invention;
[0028] Figure 3 This is the XRD test diagram of the piezoelectric ceramic prepared in Comparative Example 2 of the present invention (with impurity phase);
[0029] Figure 4 This is a scanning electron microscope image of a cross section of a piezoelectric ceramic prepared in Comparative Example 2 of the present invention;
[0030] Figure 5 The graphs are temperature stability of dielectric loss of piezoelectric ceramics prepared in the embodiments of the present invention (average value) and the comparative examples and stability curves under high power environment;
[0031] Figure 6 The graphs are the temperature stability of the piezoelectric constant of the piezoelectric ceramics prepared in the embodiments of the present invention (average value) and the comparative example and the stability curves under high power environment. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following embodiments, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. The ratios described below are all molar ratios. In special cases, the purity of the drugs used is not less than chemical purity.
[0033] The present application embodiment provides a preparation method of a high-power piezoelectric ceramic, which comprises the following steps: using one of zirconium dioxide, zirconium nitrate and zirconium acetate as a zirconium source; using one of titanium dioxide, titanium oxalate and titanium citrate as a titanium source; using one of lead tetroxide, lead nitrate and lead peroxide as a lead source; mixing two of the water-soluble raw materials in a proportion and obtaining a precursor solution; and then mixing the precursor solution with a non-water-soluble raw material and one or more of manganese antimonate and magnesium niobate, manganese niobate and zinc niobate as hard impurity factors; and one or more of bismuth manganate, bismuth ferrite, bismuth scandate and calcium ferrite as high-temperature impurity factors; and then ball milling the mixture to obtain a ceramic slurry; spray drying the mixture to obtain a primary powder; and finally performing a solid-phase reaction at a certain temperature to obtain a target powder; and then pressing, sintering, applying electrodes and polarizing the mixture to obtain a high-power high-temperature resistant piezoelectric ceramic. The above process comprises the following steps:
[0034] 1) Determine the ceramic matrix formula as Pb(Zr x Ti (1-x) )O3, 0.4≤x≤0.6, weighing two of the water-soluble zirconium source, titanium source, and lead source according to a specified stoichiometric ratio (molar ratio), dissolving them in deionized water, and mixing the two evenly to obtain a precursor solution;
[0035] 2) According to the stoichiometric ratio in the matrix formula 1), weigh the remaining non-water-soluble raw material and add it to the precursor solution, mix and stir to obtain a suspension A;
[0036] 3) According to the mass ratio of doping factor: matrix formula = 0.1~10%, the mass ratio of hard doping factor: high temperature doping factor = 0.5~2 (when adding multiple hard doping factors at the same time, the mass is evenly divided, and the high temperature doping factor is as above), add the weighed dopant to the suspension, mix and stir evenly to obtain suspension B;
[0037] 4) Use deionized water to adjust the solid content (solid mass content) of suspension B to 40-80%;
[0038] 5) ball milling the suspension B for 60-200 min to obtain a ceramic slurry with a solid particle D50 of 0.5-2 μm;
[0039] 6) spray drying the ceramic slurry to obtain primary powder;
[0040] 7) Place the primary powder in a sealed box-type high-temperature sintering furnace, heat at 600-1000°C for 1-4 hours at a heating rate of 3-5°C / min, cool naturally after the reaction, crush and grind the bulk powder, and obtain the target ceramic powder after passing through a 120-mesh sieve;
[0041] 8) The ceramic powder is further pressed, sintered, electroded and polarized to obtain high-power high-temperature resistant piezoelectric ceramics, specifically:
[0042] Pressing: molded under 200Mpa pressure Ceramic greenware;
[0043] Sintering: The ceramic green body was fired at 1250℃ for 4h;
[0044] Electrode: Silver is coated on the surface of the blank using screen printing technology and fired at 800℃ for 10 minutes;
[0045] Polarization: The green sheets were polarized at 120°C using a voltage of 3 kV / mm.
[0046] Embodiment 1:
[0047] According to the general formula Pb(Zr x Ti (1-x))O3, taking x=0.4, weighing zirconium nitrate and titanium oxalate according to the specified stoichiometric ratio (molar ratio), dissolving them in deionized water and mixing evenly, adding lead tetroxide weighed according to the stoichiometric ratio (molar ratio) and mixing evenly, and then adding dopants with a mass ratio of 0.1%, wherein the hard impurity factors are manganese antimonate and magnesium niobate, and the high-temperature impurity factors are bismuth manganate and calcium ferrite, and the mass ratio of the two is 0.5, adjusting the solid content to 50%, ball milling for 60 minutes, spray drying to obtain the initial powder, heating the reaction at 700°C at a heating rate of 3°C / min for 4 hours to obtain ceramic powder, and then pressing, sintering, electrode application and polarization to obtain high-power high-temperature resistant piezoelectric ceramics.
[0048] After XRD testing and SEM observation, the results are as follows Figure 1 to Figure 2 As shown, it is shown that the piezoelectric ceramic obtained by the method of this embodiment has a pure phase structure.
[0049] Embodiment 2:
[0050] The zirconium source, titanium source and lead source are lead nitrate, titanium citrate and zirconium dioxide, the hard impurity factors are manganese antimonate and zinc niobate, and the high temperature impurity factors are calcium ferrite and bismuth scandate. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0051] Embodiment 3:
[0052] The zirconium source, titanium source and lead source are zirconium nitrate, titanium oxalate and lead peroxide, the hard impurity factor is magnesium niobate, and the high-temperature impurity factor is bismuth ferrite. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0053] Embodiment 4:
[0054] The zirconium source, titanium source and lead source are zirconium nitrate, lead nitrate and titanium dioxide, the hard impurity factors are magnesium niobate and zinc niobate, and the high temperature impurity factor is bismuth scandate. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0055] Embodiment 5:
[0056] The zirconium source, titanium source and lead source are zirconium acetate, titanium citrate and lead peroxide, the hard impurity factor is zinc niobate, and the high temperature impurity factor is bismuth manganate and calcium ferrite. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0057] Embodiment 6:
[0058] The zirconium source, titanium source and lead source are lead nitrate, titanium oxalate and zirconium dioxide, the hard impurity factors are zinc niobate, magnesium niobate and manganese antimonate; the high temperature impurity factor is bismuth scandate, and the relevant experimental parameters are shown in Table 1. The rest are the same as Example 1.
[0059] Embodiment 7:
[0060] The zirconium source, titanium source and lead source are zirconium acetate, titanium citrate and lead peroxide, the hard impurity factor is manganese niobate, and the high-temperature impurity factor is calcium ferrite. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0061] Embodiment 8:
[0062] The zirconium source, titanium source and lead source are zirconium acetate, lead nitrate and titanium dioxide, the hard impurity factor is zinc niobate, and the high temperature impurity factor is calcium ferrite, bismuth ferrite and bismuth scandate. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0063] Embodiment 9:
[0064] The zirconium source, titanium source and lead source are lead acetate, titanium citrate and zirconium dioxide, the hard impurity factor is manganese antimonate, and the high-temperature impurity factor is bismuth scandate. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0065] Embodiment 10:
[0066] The zirconium source, titanium source and lead source are zirconium nitrate, titanium oxalate and lead peroxide, the hard impurity factors are manganese antimonate and zinc niobate, and the high temperature impurity factor is bismuth scandate. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0067] Embodiment 11:
[0068] The zirconium source, titanium source and lead source are lead nitrate, zirconium acetate and titanium dioxide, the hard impurity factor is magnesium niobate, and the high temperature impurity factor is bismuth scandate and bismuth manganate. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0069] Embodiment 12:
[0070] The zirconium source, titanium source and lead source are zirconium nitrate, titanium citrate and lead peroxide, the hard impurity factor is manganese niobate, and the high-temperature impurity factor is bismuth ferrite. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0071] Embodiment 13:
[0072] The zirconium source, titanium source and lead source are zirconium nitrate, titanium citrate and lead tetroxide, the hard impurity factor is zinc niobate, and the high temperature impurity factor is bismuth ferrite and calcium ferrite. The relevant experimental parameters are shown in Table 1, and the rest are the same as Example 1.
[0073] Embodiment 14:
[0074] The zirconium source, titanium source and lead source are lead nitrate, titanium citrate and zirconium dioxide, the hard impurity factors are magnesium niobate and manganese antimonate; the high temperature impurity factor is bismuth ferrite, and the relevant experimental parameters are shown in Table 1. The rest are the same as Example 1.
[0075] Table 1 Parameters related to Examples 1 to 14
[0076]
[0077] Comparative Example 1: According to the general formula Pb(Zr x Ti (1-x) ) O3, taking x=0.4, weighing and mixing lead tetroxide, zirconium dioxide and titanium dioxide according to the stoichiometric ratio (molar ratio) of the chemical formula and placing them in a ball mill, drying the mixture, preparing ceramic powder according to the solid phase synthesis method, and then obtaining high-power high-temperature resistant piezoelectric ceramics through pressing, sintering, electrode application and polarization.
[0078] Comparative Example 2: According to the general formula Pb(Zr x Ti (1-x) ) O3, take x=0.52, weigh and mix lead tetroxide, zirconium dioxide and titanium dioxide according to the stoichiometric ratio (molar ratio) of the chemical formula, and then add 3% of the dopant by mass, among which the hard impurity factors are magnesium niobate and manganese antimonate, and the high-temperature impurity factor is bismuth ferrite, and the mass ratio of the two is 1, put them in a ball mill, dry the mixture, and prepare ceramic powder according to the solid phase synthesis method, and then obtain high-power high-temperature resistant piezoelectric ceramics through pressing, sintering, electrode application and polarization. After xrd testing and scanning electron microscope photography, the results are as follows Figure 3 to Figure 4 As shown, it is shown that the piezoelectric ceramic structure obtained by the comparative example method has a mixed phase.
[0079] Comparative Example 3: According to the general formula Pb(Zr x Ti (1-x) ) O3, taking x=0.4, weighing zirconium nitrate and titanium oxalate according to the specified stoichiometric ratio (molar ratio), dissolving them in deionized water and mixing evenly, adding lead tetroxide weighed according to the stoichiometric ratio (molar ratio) and mixing evenly, adjusting the solid content to 70% and ball milling for 60 minutes, spray drying to obtain primary powder, heating the reaction at 800°C at a heating rate of 3°C / min for 4 hours to obtain ceramic powder, and then pressing, sintering, applying electrodes and polarization to obtain high-power high-temperature resistant piezoelectric ceramics.
[0080] Comparative Example 4: According to the general formula Pb(Zr x Ti (1-x)) O3, taking x=0.46, weighing zirconium nitrate and titanium oxalate according to the specified stoichiometric ratio (molar ratio), dissolving them in deionized water and mixing them evenly, adding lead tetroxide weighed according to the stoichiometric ratio (molar ratio) and mixing them evenly, then adding 3% of dopants by mass, wherein the hard impurity factors are manganese antimonate and zinc niobate, adjusting the solid content to 50%, ball milling for 80 minutes, spray drying to obtain initial powder, heating the reaction at 700°C at a heating rate of 4°C / min for 4 hours to obtain ceramic powder, and then pressing, sintering, electrode application and polarization to obtain high-power high-temperature resistant piezoelectric ceramics.
[0081] Comparative Example 5: According to the general formula Pb(Zr x Ti (1-x) ) O3, taking x=0.52, weighing and mixing lead tetroxide, zirconium dioxide and titanium dioxide according to the stoichiometric ratio (molar ratio) of the chemical formula, and then adding 2% of dopants by mass, wherein the hard impurity factors are magnesium niobate and manganese antimonate, placing in a ball mill, drying the mixture, preparing ceramic powder by solid phase synthesis method, and then obtaining high-power high-temperature resistant piezoelectric ceramics through pressing, sintering, electrode application and polarization.
[0082] Comparative Example 6: According to the general formula Pb(Zr x Ti (1-x) ) O3, taking x=0.44, weighing zirconium nitrate and titanium oxalate according to the specified stoichiometric ratio (molar ratio), dissolving them in deionized water and mixing them evenly, adding lead tetroxide weighed according to the stoichiometric ratio (molar ratio) and mixing them evenly, then adding dopants with a mass ratio of 3%, wherein the high-temperature doping factors are bismuth ferrite and calcium ferrite, adjusting the solid content to 60%, ball milling for 80 minutes, spray drying to obtain initial powder, heating the reaction at 700°C at a heating rate of 4°C / min for 4 hours to obtain ceramic powder, and then pressing, sintering, electrode application and polarization to obtain high-power high-temperature resistant piezoelectric ceramics.
[0083] Comparative Example 7: According to the general formula Pb(Zr x Ti (1-x) ) O3, taking x=0.5, weighing and mixing lead tetroxide, zirconium dioxide and titanium dioxide according to the stoichiometric ratio (molar ratio) of the chemical formula, and then adding 2% of dopants by mass, wherein the high-temperature doping factor is bismuth ferrite, placing in a ball mill, drying the mixture, preparing ceramic powder by solid phase synthesis method, and then obtaining high-power high-temperature resistant piezoelectric ceramics through pressing, sintering, electrode application and polarization.
[0084] Comparative Example 8: According to the general formula Pb(Zr x Ti (1-x)) O3, taking x=0.48, weighing and mixing lead peroxide, zirconium dioxide and titanium dioxide according to the stoichiometric ratio (molar ratio) of the chemical formula, and then adding 5% of dopants by mass, wherein the hard impurity factor is manganese niobate, and the high-temperature impurity factors are calcium ferrite and bismuth ferrite, and the mass ratio of the two is 1.5, placing in a ball mill, drying the mixture, preparing ceramic powder by solid phase synthesis method, and then obtaining high-power high-temperature resistant piezoelectric ceramics through pressing, sintering, electrode application and polarization.
[0085] Comparative Example 9: According to the general formula Pb(Zr x Ti (1-x) ) O3, taking x=0.6, lead peroxide, zirconium dioxide and titanium dioxide are weighed and mixed according to the stoichiometric ratio (molar ratio) of the chemical formula, and then 5% of dopants are added, wherein the hard impurity factors are magnesium niobate and zinc niobate, and the high-temperature impurity factors are bismuth scandate and calcium ferrite, and the mass ratio of the two is 2. The mixture is placed in a ball mill, dried, and ceramic powder is prepared by solid phase synthesis method, and then high-power high-temperature resistant piezoelectric ceramics are obtained through pressing, sintering, electrode application and polarization.
[0086] Comparative Example 10: According to the general formula Pb(Zr x Ti (1-x) ) O3, taking x=0.55, lead peroxide, zirconium dioxide and titanium dioxide are weighed and mixed according to the stoichiometric ratio (molar ratio) of the chemical formula, and then 8% of dopants are added, among which the hard impurity factors are manganese niobate, magnesium niobate and zinc niobate, and the high-temperature impurity factor is calcium ferrite, and the mass ratio of the two is 1.2. The mixture is placed in a ball mill, dried, and ceramic powder is prepared by solid phase synthesis method, and then high-power high-temperature resistant piezoelectric ceramics are obtained through pressing, sintering, electrode application and polarization.
[0087] Comparative Example 11: According to the general formula Pb(Zr x Ti (1-x) ) O3, taking x=0.46, weighing and mixing lead tetroxide, zirconium dioxide and titanium dioxide according to the stoichiometric ratio (molar ratio) of the chemical formula, and then adding dopants with a mass ratio of 10%, wherein the hard impurity factors are manganese antimonate and zinc niobate, and the high-temperature impurity factor is bismuth manganate, the mass ratio of the two is 0.5, placing in a ball mill, the mixture is dried, and the ceramic powder is prepared by the solid phase synthesis method, and then subjected to pressing, sintering, electrode application and polarization treatment to obtain high-power high-temperature resistant piezoelectric ceramics.
[0088] For ease of comparison, the main relevant parameters of Comparative Examples 1 to 11 are listed in Table 2:
[0089] Table 2 Related parameters of Comparative Examples 1 to 11
[0090]
[0091] The piezoelectric ceramics prepared in all embodiments and comparative examples of the present invention were subjected to dielectric loss tests, and the dielectric loss test standards referred to were: GB / T 15750-2008, GB / T 3389-2008. The test results were compared in a table 3, and the results showed that under different temperature and voltage conditions, the dielectric loss of the piezoelectric ceramics prepared in the embodiments was significantly smaller, and the dielectric loss at low temperature and low pressure was about 77% of that of the comparative example (tanδ (%) - 25°C, 1V / mm), and the dielectric loss at high temperature and high pressure was only about 57% of that of the comparative example (tanδ (%) - 85°C, 400V / mm).
[0092] Table 3 Dielectric loss value test results
[0093]
[0094] The piezoelectric constant of the piezoelectric ceramics prepared in all the embodiments and comparative examples of the present invention was tested, and the piezoelectric constant (d33) was tested in accordance with the test standards: GB / T 15750-2008, GB / T 3389-2008. The comparison of the test results is shown in Table 4. The results show that under different temperature and voltage conditions, the piezoelectric constant of the piezoelectric ceramics prepared in the embodiments is better, and the decrease in high temperature and high pressure conditions is lower than that of the comparative example. This is because the present application introduces a high-temperature doping factor obtained through experimental screening on the basis of adding a hard doping factor to obtain low dielectric loss and high-voltage electrical performance, thereby improving the stability of the product under high temperature and high power conditions. The hard doping factor and the high-temperature doping factor complement each other, so that the high-power piezoelectric ceramics obtained have obvious high temperature resistance.
[0095] Table 4 Piezoelectric constant test results
[0096]
[0097] The above embodiments and test experiments show that the piezoelectric ceramics prepared by the method of the embodiment of the present application have a better pure phase structure and a tighter grain boundary than the piezoelectric ceramics prepared by the comparative method. The dielectric loss test and piezoelectric constant test results show that the piezoelectric ceramics prepared by the method of the embodiment of the present application have lower dielectric loss and higher piezoelectric constant under high temperature and high pressure, and better performance. Figure 5 to Figure 6 As shown, it is shown that the material prepared by the method of the present invention is a high-power high-temperature resistant piezoelectric ceramic.
Claims
1. A method for preparing a high-power high-temperature resistant piezoelectric ceramic, characterized in that: The high-power high-temperature resistant piezoelectric ceramic is a lead zirconate titanate piezoelectric ceramic with an impurity factor added, and the general formula of the matrix is: Pb(Zr x Ti (1-x) )O3, wherein 0.4≤x≤0.6, the impurity factor is specifically a hard impurity factor and a high temperature impurity factor, and the preparation method comprises the following steps: According to the matrix general formula, two of the water-soluble zirconium source, titanium source and lead source are weighed and dissolved in deionized water and stirred to form a solution, and one of the water-insoluble zirconium source, titanium source and lead source is added and mixed with the doping factor to obtain a suspension; ball milling the suspension to obtain a ceramic slurry; The ceramic slurry is spray-dried to obtain primary powder; The primary powder is placed in a sealed high-temperature sintering furnace for heating reaction to obtain a ceramic powder; The ceramic powder is subjected to pressing, sintering, electrode application and polarization treatment to obtain a high-power high-temperature resistant piezoelectric ceramic; The hard impurity factor is one or more of manganese antimonate, magnesium niobate, manganese niobate, and zinc niobate; the high temperature impurity factor is one or more of bismuth manganate, bismuth ferrite, bismuth scandate, and calcium ferrite; The content of the impurity factor is 0.1-10wt% of the matrix, and the mass ratio of the hard impurity factor to the high temperature impurity factor is 0.5-2:1; The suspension is adjusted to a solid content of 40-80% using deionized water; The D50 of the solid material particles in the ceramic slurry is 0.5-2 μm; The specific conditions of the heating reaction are: reaction at 600-1000° C. for 1-4 hours and a heating rate of 3-5° C. / min.
2. The method for preparing high-power high-temperature resistant piezoelectric ceramics according to claim 1, characterized in that: The zirconium source is one or more of zirconium dioxide, zirconium nitrate, and zirconium acetate; the titanium source is one or more of titanium dioxide, titanium oxalate, and titanium citrate; and the lead source is one or more of lead tetroxide, lead nitrate, and lead peroxide.
3. The method for preparing high-power high-temperature resistant piezoelectric ceramics according to claim 1, characterized in that: When there are two or more hard impurity factors, the masses of all hard impurity factors are equal.
4. The method for preparing high-power high-temperature resistant piezoelectric ceramics according to claim 1, characterized in that: When there are two or more high-temperature doping factors, the qualities of all high-temperature doping factors are equal.
5. The method for preparing high-power high-temperature resistant piezoelectric ceramics according to claim 1, characterized in that: The ball milling time is 60-200 min.
6. The product obtained by the preparation method of the high-power high-temperature resistant piezoelectric ceramic according to any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method of lead zirconate titanate piezoelectric ceramics
CN102718484A
Preparation method of multi-component lead zirconate titanate based piezoelectric ceramic element
CN103524130A